The Emergence and Evolution of Social Networking Sites as an Organizational Form. (August 2016) - Weber, Matthew S.; Fulk, Janet; Monge, Peter
A number of new organizational structures have emerged in recent years, including peer production networks, digitally organized social movements, and social networking sites (SNSs). Researchers have devoted considerable attention to these phenomena as groups and communities. This article takes a complementary approach by conceptualizing them as organizational forms, with focus on the emergence of SNSs as a distinct organizational form. Community ecology theory is implemented to explicate the emergence and subsequent legitimation of organizational forms, providing a foundation for understanding how new forms emerge through interaction with the surrounding environment. Industry data and historical records are utilized to illustrate the development of one specific form: online SNSs. This analysis demonstrates that legitimation is an ongoing process of replication of features, but legitimacy also occurs through recognition from adjacent populations. Findings illustrate the validity of alternative processes of form legitimacy.